Obstacles along the path of women enterprises in Africa: A case study of Ogotun women in Ekiti state, Nigeria - Emmanuel F. Jaiyeola; Mercy Modupe Adeyeye (Heliyon, 2021)
African women have a history of entrepreneurship dating back to the pre-colonial era, but in this 21st century, women in Africa are assessed by the World Bank to be at the lower deck of economic breakthrough in comparison to men. Although both men and women operate in the same business climate, women are usually poorer and are harder hit by adverse economic situations. Oftentimes, they self-develop their businesses and skills; they also seek, create and self-fund opportunities, but these efforts are usually met with huge obstacles and barriers. Therefore, this study aims to identify some of the obstacles and barriers plaguing the success and growth of women entrepreneurial activities and proffer solutions that could ameliorate the problems. The study uses a qualitative case study research design to uncover the experiences of women in a rural community of southwestern Nigeria. The data for analysis were collected through twenty in-depth interviews, two participants observations, and four focus group discussions. Some documents were analyzed to triangulate the data sources to ensure credibility. Findings include obstacles such as a traditional patriarchal culture that inhibits women from achieving personal development, complete subordination to male domination, colonial vestiges that gendered entrepreneurship in Africa, and lack of support by male-dominated government. The implication of these is that women continue to struggle to develop their entrepreneurial activities without much breakthrough. They remain economically impoverished and suffer greatly to care for themselves and their families, and to be part of social development. The study recommends that relevant organizations and government continue to work to develop strategies to remove these barriers.